Halal FinTech Models and Sharia MSME Strengthening: Digital Financial Inclusion in Indonesia - Ahmad Syaifullah; Athia Nur Kamilah; Ade Sofyan Mulazid (Ethiconomics: Journal of Islamic Banking and Finance, 2026)
The rapid expansion of digital finance in the Society 5.0 era has reshaped how Sharia-based Micro, Small, and Medium Enterprises (MSMEs) access capital, conduct transactions, and manage business operations. Despite the strong demographic potential of Muslim-majority markets, Sharia MSMEs continue to face persistent barriers in financial inclusion, including limited access to formal financing, low digital literacy, and weak integration with halal value chains. This study examines the role of Halal FinTech business models in strengthening Sharia MSMEs and formulates strategies for digital financial inclusion. Using a mixed-methods approach, the research surveyed 312 Sharia MSME actors across five major regions in Indonesia and conducted in-depth interviews with 18 key informants from FinTech operators, regulators, and Islamic financial scholars. Quantitative data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS), while qualitative data were analyzed thematically. The findings reveal that Halal FinTech business models particularly peer-to-peer financing, equity crowdfunding, and Sharia digital payment platforms significantly contribute to the strengthening of Sharia MSMEs through three primary mechanisms: improved capital accessibility, enhanced operational efficiency, and broader market reach. The integration of Sharia compliance, digital literacy programs, and human-centered technology characteristic of Society 5.0 emerges as a strategic foundation for inclusive growth. The study contributes a novel framework that aligns Halal FinTech business architecture with maqashid sharia principles and digital ecosystem requirements.